2016
DOI: 10.1136/gutjnl-2015-310249
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic mucosal resection for large serrated lesions in comparison with adenomas: a prospective multicentre study of 2000 lesions

Abstract: ClinicalTrials.gov NCT01368289.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
107
3
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 38 publications
13
107
3
4
Order By: Relevance
“…This recommendation is based on the higher risk of incomplete resection and complications associated with removal of large sessile polyps in the right colon and some evidence of a favourable effect of a threshold volume for better outcomes 102–104. These data, combined with variability in SL detection and assessment (see statements 13 and 14), and data on comparing the similar outcomes on safety of endoscopic resection in adenomas and SSLs,105 suggest a significant role for operator variability and outcomes in the management of these lesions. Therefore, for larger lesions ≥10 mm endoscopists should meet the competencies and standards set out in the BSG 2015 guidelines on management of large non-polypoid colorectal polyps 104…”
Section: Detection and Resection Of Slsmentioning
confidence: 99%
“…This recommendation is based on the higher risk of incomplete resection and complications associated with removal of large sessile polyps in the right colon and some evidence of a favourable effect of a threshold volume for better outcomes 102–104. These data, combined with variability in SL detection and assessment (see statements 13 and 14), and data on comparing the similar outcomes on safety of endoscopic resection in adenomas and SSLs,105 suggest a significant role for operator variability and outcomes in the management of these lesions. Therefore, for larger lesions ≥10 mm endoscopists should meet the competencies and standards set out in the BSG 2015 guidelines on management of large non-polypoid colorectal polyps 104…”
Section: Detection and Resection Of Slsmentioning
confidence: 99%
“…First, all medico-economic estimations were based on a recurrence rate of 14% after WF piecemeal EMR. In a previous study of their group,5 they reported a higher recurrence rate (>30%) in lesions greater than 4 cm. This cut-off size is probably closer to the mean size of lesions generally resected by ESD in Western countries, and lesions between 2 and 4 cm could be good targets for hybrid resection techniques to reach R0 with more simple procedures 7 8.…”
mentioning
confidence: 78%
“…ESDs are associated with a high en bloc resection rate, low risk of recurrence and perfect pathological analysis 4. Defenders of piecemeal EMR point out the higher risk of ESD, the long duration of procedures, the discrepancies between Eastern and Western series, and the low proportion of lesions with superficial submucosal cancer 5. They also point out the good results of wide-field (WF)-EMR for complete eradication even when several sessions are needed 6.…”
mentioning
confidence: 99%
“…Prior studies that have evaluated risk factors for incomplete resection of large colonic polyps have included only specialized endoscopists at their center, while our study included general and specialist endoscopists, which may explain the higher rate of IR [13, 21]. Another reason may be our study’s higher percentage of polyps ≥ 40 mm, which is a known risk factor for IR.…”
Section: Discussionmentioning
confidence: 99%